Effectiveness of a multisite personal protective equipment (PPE)–free zone intervention in acute care. (July 2019) - Visnovsky, Lindsay D.; Zhang, Yue; Leecaster, Molly K.; Safdar, Nasia; Barko, Lauren; Haroldsen, Candace; Mulvey, Diane L.; Nevers, McKenna; Shaughnessy, Catherine; Stratford, Kristina M.; Drews, Frank A.; Samore, Matthew H.; et al.
Abstract: Objective: Determine the effectiveness of a personal protective equipment (PPE)-free zone intervention on healthcare personnel (HCP) entry hand hygiene (HH) and PPE donning compliance in rooms of patients in contact precautions. Design: Quasi-experimental, multicenter intervention, before-and-after study with concurrent controls. Setting: All patient rooms on contact precautions on 16 units (5 medical-surgical, 6 intensive care, 5 specialty care units) at 3 acute-care facilities (2 academic medical centers, 1 Veterans Affairs hospital). Observations of PPE donning and entry HH compliance by HCP were conducted during both study phases. Surveys of HCP perceptions of the PPE-free zone were distributed in both study phases. Intervention: A PPE-free zone, where a low-risk area inside door thresholds of contact precautions rooms was demarcated by red tape on the floor. Inside this area, HCP were not required to wear PPE. Results: We observed 3, 970 room entries. HH compliance did not change between study phases among intervention units (relative risk [RR], 0.92; P = .29) and declined in control units (RR, 0.70; P = .005); however, the PPE-free zone did not significantly affect compliance ( P = .07). The PPE-free zone effect on HH was significant only for rooms on enteric precautions ( P = .008). PPE use was not significantly different before versus after the intervention ( P = .15). HCP perceived the zone positively; 65% agreed that it facilitated communication and 66.8% agreed that it permitted checking on patients more frequently. Conclusions: HCP viewed the PPE-free zone favorably and it did not adversely affect PPE or HH compliance. Future infection prevention interventions should consider the complex sociotechnical system factors influencing behavior change.